PENGARUH MEDIA AUDIO TERHADAP PENINGKATAN PENGETAHUAN PENCEGAHAN DIABETES MELITUS TIPE 2 PADA REMAJA (Politeknik Kesehatan Kemenkes Bandung, 2021)
The prevalence of Diabetes Mellitus in Indonesia based on a doctor's diagnosis at the age of 15 years is 2%. The number of people with Diabetes Mellitus in West Java is 52,511 cases, while in Bandung it is 2,849 cases. Type 2 diabetes mellitus usually affects elderly individuals, but adolescents can also be affected by diabetes mellitus. WHO (2017) defines adolescence as a period of human development after childhood and before adulthood in the age range of 10-19 years. Therefore, it is necessary to prevent type 2 diabetes mellitus from an early age in adolescents by providing health education regarding the prevention of type 2 diabetes mellitus through audio media. Knowing the effect of audio media on knowledge of prevention of type 2 diabetes mellitus in class X adolescents at SMAN 9 Bandung. This type of research uses a pre- experimental design with one group pre-test-post-test design without control to a sample of 78 adolescents. The results of this study indicate the average value of knowledge before being given audio media is 62.49 and after being given audio media is 76.92, it can be concluded that there is an increase in the average knowledge of students by 23%. Data obtained by Kolmogrof Smirnov statistical test to determine the normality of the data, and Paired T-test to determine the effect between two variables that are normally distributed. Based on the Paired T-test, p value <0.05 was obtained. Audio media has an effect on increasing adolescent knowledge about prevention of type 2 diabetes mellitus. Audio media can be used as a tool to provide health education to adolescents to increase knowledge about prevention of type 2 diabetes mellitus.